IMPLEMENTASI UJIAN AKHIR MADRASAH BERSTANDAR DAERAH BERBASIS KOMPUTER (UAMBD-BK) DI MADRASAH - Multazem Aji Busono; Moch. Imam Machfudi (Nurul Jadid University, 2019)
The using of technology in learning activities, especially computer technology provides convenience to educators to explain learning materials to students to be easy, effective and efficient. This study uses qualitative methods with a case study approach. The results showed that the implementation of the final examination of the computer-based regional standard madrasah held at MI Muhammadiyah Ledoktempuro Randuagung and Randuagung Lumajang Subdistrict MI Nurul Islam Gedangmas was carried out through three stages; Pre Implementation, Implementation, and Post-Implementation UAMBD-BK with the use of the internet network.